2014
DOI: 10.3390/ijms151221803
|View full text |Cite
|
Sign up to set email alerts
|

Physiological and Proteomic Analysis in Chloroplasts of Solanum lycopersicum L. under Silicon Efficiency and Salinity Stress

Abstract: Tomato plants often grow in saline environments in Mediterranean countries where salt accumulation in the soil is a major abiotic stress that limits its productivity. However, silicon (Si) supplementation has been reported to improve tolerance against several forms of abiotic stress. The primary aim of our study was to investigate, using comparative physiological and proteomic approaches, salinity stress in chloroplasts of tomato under silicon supplementation. Tomato seedlings (Solanum lycopersicum L.) were gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
52
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 105 publications
(55 citation statements)
references
References 62 publications
(76 reference statements)
2
52
0
1
Order By: Relevance
“…Current high-throughput proteomic approaches are powerful to untangle the complicated mechanisms of chloroplast development, metabolism and stress response [7-10]. More than 522 NaCl-responsive chloroplast proteins were found in different plant species, such as tomato ( Solanum lycopersicum ) [11], wheat ( Triticum aestivum ) [12], and other plant species [13-18]. The presence of these proteins indicate that the light harvesting, photosynthetic electron transfer, carbon assimilation, ROS homeostasis, energy metabolism, signaling, and membrane trafficking were modulated in chloroplasts in response to NaCl stress.…”
Section: Introductionmentioning
confidence: 99%
“…Current high-throughput proteomic approaches are powerful to untangle the complicated mechanisms of chloroplast development, metabolism and stress response [7-10]. More than 522 NaCl-responsive chloroplast proteins were found in different plant species, such as tomato ( Solanum lycopersicum ) [11], wheat ( Triticum aestivum ) [12], and other plant species [13-18]. The presence of these proteins indicate that the light harvesting, photosynthetic electron transfer, carbon assimilation, ROS homeostasis, energy metabolism, signaling, and membrane trafficking were modulated in chloroplasts in response to NaCl stress.…”
Section: Introductionmentioning
confidence: 99%
“…As a result of this imbalance, levels of reactive oxygen species increase, while plant growth and yield decline (Liang et al, 2015). It has been widely reported that the application of Si to plants may increase salt tolerance among many important agricultural crops, such as wheat (Ahmad, 2014;Gurmani et al, 2013a), rice (Gong et al, 2006;Gurmani et al, 2013b;Kim et al, 2014), maize (Kochanov a et al, 2014;Xie et al, 2015), barley (Liang et al, 2005), sorghum (Kafi et al, 2011;Yin et al, 2013), tomato (Liang et al, 2015;Muneer et al, 2014), and soybean (Lee et al, 2010). In this study, we investigate the effect of Si (grown under two salinity regimes) on two pepper cultivars, one salt-tolerant and the other saltsensitive.…”
mentioning
confidence: 99%
“…Deficiency of these minerals especially N, may cause inhibition in the formation of chlorophyll molecules under increased salinity stress (Huang et al, 2004). Moreover, high concentration of salts in the leaves might have caused overproduction of reactive oxygen species (ROS) and forced the chloroplast to destroy all protein component of chloroplast (Muneer et al, 2014). However, rhizobial inoculation resulted in improved chlorophyll contents a, b, and carotenoids compared to respective un-inoculated controls.…”
Section: Discussionmentioning
confidence: 99%